Empowerment of Posyandu Cadres in Early Detection of Child Growth Problems: Optimization of KIA Books - Alfi Muntafiah; Octavia Permata Sari; Nor Sri Inayati; Qodri Santosa (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Posyandu (integrated health center) as a health information center for the community is expected to be the spearhead of early detection of developmental disorders in children under five. Posyandu activities are driven by cadres. Cadres monitor the growth of children under five through anthropometric measurements: body weight, height, head circumference and development milestones. Knowing how to measure anthropometric parameters, data plotting on a growth chart in the Maternal and Child Health (Kesehatan Ibu dan Anak=KIA) book, and interpret the results are very important. Cadres with good understanding and skills will greatly assist in monitoring child growth and development. This activity is expected to increase the knowledge and skills of cadres in monitoring child development. This activity was carried out through counseling, training, case study, and discussion. Pre-tests and post-tests were conducted to evaluate this activity. The mean pre-test was 40.00 ± 11.69, with the lowest value being 10.00 and the highest value being 60.00. The mean post-test was 54.10 ± 12.08, the lowest value was 30.00 and the highest was 90.00. The Wilcoxon test found p=000, where 20.5% participants' knowledge did not change while 69.23% had better knowledge compared to before the activity. Conclusion: This training can significantly improve cadres' knowledge and skills about the use of the KIA book.